Door to disposition times for obstetric triage visits: Is there a July phenomenon?. (17th February 2016) - Mehra, S.; Gavard, J. A.; Gross, G.; Myles, T.; Nguyen, T.; Amon, E.
Abstract : The July phenomenon refers to a change in patient outcomes within teaching hospitals with the arrival of new and inexperienced house staff at the start of the academic year (July to June). In our obstetric triage unit we retrospectively evaluated the door to disposition time (DTDT) for 1817 patients who presented across July, December and May of academic years 2009–2010 and 2010–2011. DTDT was examined for three visit levels: non-urgent, urgent and emergent. No significant differences in disposition time were found for emergent visits. For urgent visits the median DTDT significantly decreased from 171 min in July to 155 min in December and 135 min in May ( p < 0.001). Similarly for non-urgent visits, the median DTDT was greater during July than May (179 min vs. 133 min; p < 0.05). Electronic medical records (EMRs) were implemented in November 2010. Following the introduction of EMR shorter DTDT was seen in December 2010 versus December 2009 (median, 171 min vs. 150 min; p < 0.05), respectively. Our findings suggest a 'July Phenomenon' of greater disposition intervals for urgent and non-urgent obstetric triage visits across the academic year. Additionally the use of EMRs may facilitate patient flow through the OB triage unit.